Entrepreneurship Ecosystem in the Middle East and North Africa (MENA) Dynamics in Trends, Policy and Business Environment (Contributions to Management Science, 2018)
This contributed volume explores and reveals the dynamics, strengths and weaknesses, trends and implications of entrepreneurship in the Middle East and North Africa (MENA) region. Presenting papers by respected experts in the field, it shares essential insights on the status quo of entrepreneurship and the opportunities and threats it faces in the MENA region. Topics range from development of entrepreneurial universities to international entrepreneurship, as well as emergent topics such as green entrepreneurship, sustainable entrepreneurship and youth entrepreneurship.